EFEK PEMBERIAN EKSTRAK ETANOL BUAH GANDARIA (Bouea macrophylla Griffith.) TERHADAP GAMBARAN MORFOHISTOLOGI LIMPA TIKUS PUTIH (Rattus norvegicus L.) YANG DIINDUKSI KARBON TETRAKLORIDA (CCL4) - Ahmad Baihaqi Ananda El Rawy; Husnarika Febriani; Nurlian Augustin Ningrum (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2025)
Carbon tetrachloride (CCl4) is a volatile liquid that can cause hepatotoxicity in metabolism, because it produces Reactive Oxygen Species (ROS) which can trigger inflammation and cell dysfunction. Gandaria fruit (Bouea macrophylla Griffith) is known to contain a number of antioxidant compounds that function as free radical scavengers. This study aims to determine the effect of administering ethanol extract of gandaria fruit (Bouea macrophylla Griffith.) on the morphology and histology of the spleen of white rats (Rattus norvegicus L.) induced by carbon tetrachloride (CCl4). This study used RAL using 25 rats divided into 5 groups, Negative controls was only given food and drink, Positive controls was given CCl4 1mL/kgBW Treatment P1, P2, P3, was given CCl4 1 mL/kgBW + gandaria fruit extract with doses of P1 (100 mg/kgBW), P2 (150 mg/kgBW), P3 (200 mg/kgBW). CCl4 administration was carried out every 3 days for 30 days and gandaria fruit extract was administered daily starting from day 8 to day 30.The stages in this study include qualitative phytochemical screening tests, antioxidant activity tests using the DPPH method, macroscopic analysis of the morphological condition of the spleen organ and histological examination of the spleen organ using the paraffination and HE staining methods. Data analysis used the one-way ANOVA test and continued with Duncan's advanced test. The results showed that administration of gandaria fruit ethanol extract did not affect the morphology of the spleen organ of white rats induced by carbon tetrachloride (CCl4) including the edge shape, color, surface, texture, weight, length and width. However, induction of carbon tetrachloride at a dose of 1 mL/kgBW can damage the histological condition of the spleen tissue including bleeding and necrosis and widening the diameter of the white pulp, the diameter of the germinal center and the marginal zone. Administration of gandaria fruit ethanol extract in the P3 treatment at a dose of 200 mg/kgBW was the most effective dose in repairing spleen organ tissue.